Evaluation of provided services at MRI department in a public hospital using discrete event simulation technique: A case study. Issue 1 (1st January 2017) - Shakoor, Mwafak; Al-Nasra, Moayyad; Abu Jadayil, Wisam; Jaber, Nasser; Abu Jadayil, Seham
Abstract: The main purpose of this study is to improve on the performance of a specific healthcare department in order to meet the major administrative expectation. These expectations include better serving the patients in that department in a seamless and most economical manner. This need opened the door for a full review of an existing system. In this research a radiology department in a public hospital has been selected. The quality of service, patients' medical needs, and the cost of service are the main criteria used to develop a simulation model in this study. This study uses Discrete Event Simulation as a main management tool. Collected and gathered data related to the processing time and arrival time over a period of one years are used in this study. A model was created using Arena modeling package. The model main results exhibited that the resources in the selected radiology division were exhausted. These results provided the needed tools for the management team to make managerial decisions resulting in enhancing the quality of the provided services by improving the imaging services in the radiology department. This improvement lead to reducing the patients' waiting time and at the same time improved the quality of medical provided services. The major contribution of this article is related to investigating the operation effectiveness of MRI radiology division within a healthcare system by utilizing the Arena Simulation Software. This study utilizes an optimization technique to provide the higher management team the needed tools to make efficient decisions.